The problems of students' physical training individualization - V.A. Druz; S.S. Iermakov; M.O. Nosko; L.Ye. Shesterova; N.A. Novitskaya (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to assess physical health and biological age of 1st 2nd year girl students, depending on their physical activity, as well as to work out system of control over students' health. Material: in the research 1st and 2nd year girl students (n=120) participated. Results: students' busy in their working day was analyzed as well as student's understanding of healthy life style during working day. We also paid attention to reasons of sharp weakening of students' physical fitness and determined integral indicator of healthy life style conception as well as significance of every its component. The following concepts are introduced: physical health, including individual level of physical condition; physical fitness and physical state. We found normal level for every component of physical health and correlation between population, regional and individual norms. Conclusions: For students' healthy life style formation it is necessary to observe norm requirements to all its components. Violation of any component's norm results in worsening general final result.